Spontaneous regression of locally advanced nonsmall cell lung cancer: A case report. Issue 31 (August 2018) - Ooi, Kiat Huat; Cheo, Timothy; Soon, Gwyneth Shook Ting; Leong, Cheng Nang
Abstract: Rationale: Spontaneous regression of non-small cell lung cancer is exceptionally rare. Patient concerns: Treatment-related toxicity. Diagnoses: We report a case of a patient diagnosed with locally advanced non-small cell lung cancer. Interventions: The patient declined potentially curative treatment, and did not receive any anti-cancer treatment. Outcomes: He has survived more than two years since his initial diagnosis, maintaining his good performance status. Serial imaging with computed tomography scans showed tumour regression and near-complete resolution of his disease. Lessons: Spontaneous regression of non-small cell lung cancer, by virtue of its scarcity, has not been well-studied and is poorly understood. Further studies are required, in order to clarify the mechanisms by which spontaneous regression occurs, and possibly identify new targets for cancer treatment. Abstract : Supplemental Digital Content is available in the text